Analisis Operasional Bandar Udara Ngloram sebagai Satuan Pelayanan Bandar Udara di Kabupaten Blora - Ferdianto, Muhamad Muqsith; Widagdo, Joko (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Airport Service Unit, hereinafter abbreviated as SATPEL BU, is an airport service implementation unit that is under and responsible to the Head of Airport Operations Unit Office. In this study the Ngloram Airport Service Unit is under and responsible to the Head of the Dewadaru Airport Implementation Unit Office. This study is intended to find out how the Ngloram Airport Implementation Unit operates. Operations focus on policies, structure and work assignments, as well as technical standards and operations that exist in SATPEL BU Ngloram. This research was conducted using a descriptive qualitative approach and data collection techniques through observation, interviews, documents, literature study. This study uses primary and secondary data sources. Primary data sources were obtained from civil servants and honorary staff who served in SATPEL BU, while secondary data were in the form of statutory documents, books, journals and articles related to research topics. Based on the conclusions, the results show that the operations of SATPEL BU Ngloram have been running as they should according to the regulations in charge. It's just that there is a slight inequality in terms of division of work units. According to the researcher's analysis, if the restructuring process is carried out optimally, Ngloram Airport will experience an increase in classification from SATPEL BU to become Airport Operations Unit. Keywords: Airport Service Unit (SATPEL BU), operations, policies, structure and work assignments, technical standards and operations.